Improving the Cognitive Ability of Senior High School Students on the Subject of Biological Technology Innovation through Problem Solving LKPD based on Lesson Study - Ningtyas Murni Pertiwi; Ani Sulistyarsi; Juli Sukimarwati (Magister Pendidikan Biologi, Universitas Negeri Medan, 2023)
Learning problems in class X-I SMAN 6 Madiun lead to cognitive aspects. The majority of students have not been able to achieve completeness in biological technology innovation material, students have not been actively involved, and teachers rarely use student worksheets (LKPD). This study aims to improve the cognitive abilities of students after participating in the biology learning process on biological technology innovation material using lesson study-based problem solving worksheets. The research method used was Classroom Action Research which was carried out in 3 cycles. Each cycle consists of four stages, namely planning, action, observation, and reflection which are collaborated with the lesson study stages, namely plan, do, and see. The results showed that there was an increase in the n-gain value from cycle 1 of 30.74%, cycle 2 of 49.17%, and cycle 3 of 64.36%. Strengthened by the achievement of completeness has increased from cycle 1 to cycle 2 and to cycle 3, namely from 3.45%, to 82.76%, and to 89.66%. The conclusion of this study is that the application of lesson study-based problem solving worksheets can improve students' cognitive abilities. The benefits obtained by students are that through problem solving worksheets students can improve cognitive abilities, make the learning atmosphere more enjoyable and make students active in class.